The Forecast Accuracy of Individual Analysts: Evidence of Systematic Optimism and Pessimism - Butler, Kirt C.; Lang, Larry H. P. (Journal of Accounting Research, 1991)
Analyst forecasts, Analyst forecast accuracy, Analyst competence, Systematic optimism